2020
DOI: 10.1002/ca.23614
|View full text |Cite
|
Sign up to set email alerts
|

The effect of positioning on maternal anatomy and hemodynamics during late pregnancy

Abstract: IntroductionSupine positioning during late pregnancy causes dramatic compression of maternal abdominal vasculature and is a risk factor for stillbirth. The azygos vein has been shown to provide collateral circulation in this scenario. There are many well‐known anatomical differences in abdominal vasculature between the left and right sides of the body. However, the effect of left and right positioning in pregnancy has not been well studied.Materials and MethodsAfter obtaining ethics approval, 10 women with unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…A recent study on ten pregnant women showed a 35% lower venous return in RRLP than RLLP; however, this difference in cardiac output and blood flow of the abdominal aorta (and thus the placental perfusion) is insignificant between left and right lateral decubitus positions [ 14 ]. Fujita et al analyzed thirteen pregnant women and concluded that IVC volume is most at a 30-degree tilt to the left and right in 70% and 23% of patients, respectively [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on ten pregnant women showed a 35% lower venous return in RRLP than RLLP; however, this difference in cardiac output and blood flow of the abdominal aorta (and thus the placental perfusion) is insignificant between left and right lateral decubitus positions [ 14 ]. Fujita et al analyzed thirteen pregnant women and concluded that IVC volume is most at a 30-degree tilt to the left and right in 70% and 23% of patients, respectively [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Positioning of the patient was another concern since the prone position could not be used due to pregnancy, and the right lateral position was chosen. The latter is associated with its drawbacks due to compression of the inferior vena cava, leading to reduced venous return and the risk of thromboembolism 14. The use of general anaesthesia reduces the risk of preterm labour and hence was preferred in this case.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, the patient presents transient tachycardia and late bradycardia, pallor, diaphoresis, sweating, nausea, hypotension, and dizziness in the supine position, which improves if the patient turns to the side position. This phenomenon can lead to the loss of consciousness or even sudden death of the pregnant woman in its severe form [26].…”
Section: Cardiovascular Physiological Adaptative Changes During Pregn...mentioning
confidence: 99%